Sandry's book - Pierce, Tamora (New York : Point/Scholastic, 1999)
Four young misfits find themselves living in a strictly disciplined temple community where they become friends while also learning to do crafts and to use their powers, especially magic.
Keywords: Friendship -- Juvenile fiction; Magic -- Fiction